Storage of Human Blood Platelets - Hardeman, M. R; Heynens, Carina J L. (Thrombosis and Haemostasis, 1974)
Storage experiments were performed at 4°, 25° and 37° C with platelet-rich plasma under sterile conditions. In some experiments also the effect of storing platelets at 4° C in whole blood was investigated.Before, during and after three days of storage, the platelets were tested at 37° C for their serotonin uptake and response to hypotonic shock. In addition some glycolytic intermediates were determined.A fair correlation was noticed between the serotonin uptake and hypotonic shock experiments. Both parameters were best maintained at 25° C. Also platelet counting, performed after the storage period, indicated 25° C as the best storage temperature. Determination of glycolytic intermediates did not justify any conclusion regarding the optimal storage temperature. Of the various anticoagulants studied, ACD and heparin gave the best results as to the serotonin uptake and hypotonic shock response, either with fresh or stored platelets. The use of EDTA resulted in the lowest activity, especially after storage.The results of these storage experiments in vitro, correspond well with those in vivo reported in the literature.